Myeloid and dendritic cells enhance therapeutics-induced cytokine release syndrome features in humanized BRGSF-HIS preclinical model - Martin, Gaëlle H.; Gonon, Alexis; Martin-Jeantet, Perrine; Renart-Depontieu, Florence; Biesova, Zuzana; Cifuentes, Anokhi; Mukherjee, Arnab; Thisted, Thomas; Doerner, Astrid; Campbell, Dean O.; Bourré, Ludovic; van der Horst, Edward H.; et al. (Frontiers in Immunology, 2024)
Objectives: Despite their efficacy, some immunotherapies have been shown to induce immune-related adverse events, including the potentially life-threatening cytokine release syndrome (CRS), calling for reliable and translational preclinical models to predict potential safety issues and investigate their rescue. Here, we tested the reliability of humanized BRGSF mice for the assessment of therapeutics-induced CRS features in preclinical settings. Methods: BRGSF mice reconstituted with human umbilical cord blood CD34+ cells (BRGSF-CBC) were injected with anti-CD3 antibody (OKT3), anti-CD3/CD19 bispecific T-cell engager Blinatumomab, or VISTA-targeting antibody. Human myeloid and dendritic cells' contribution was investigated in hFlt3L-boosted BRGSF-CBC mice. OKT3 treatment was also tested in human PBMC-reconstituted BRGSF mice (BRGSF-PBMC). Cytokine release, immune cell distribution, and clinical signs were followed. Results: OKT3 injection in BRGSF-CBC mice induced hallmark features of CRS, specifically inflammatory cytokines release, modifications of immune cell distribution and activation, body weight loss, and temperature drop. hFlt3L-boosted BRGSF-CBC mice displayed enhanced CRS features, revealing a significant role of myeloid and dendritic cells in this process. Clinical CRS-managing treatment Infliximab efficiently attenuated OKT3-induced toxicity. Comparison of OKT3 treatment's effect on BRGSF-CBC and BRGSF-PBMC mice showed broadened CRS features in BRGSF-CBC mice. CRS-associated features were also observed in hFlt3L-boosted BRGSF-CBC mice upon treatment with other T-cell or myeloid-targeting compounds. Conclusions: These data show that BRGSF-CBC mice represent a relevant model for the preclinical assessment of CRS and CRS-managing therapies. They also confirm a significant role of myeloid and dendritic cells in CRS development and exhibit the versatility of this model for therapeutics-induced safety assessment.